A Subjective and Objective Analysis of Pain in Female Brick Kiln Workers of West Bengal, India - Ray Chaudhuri, Subhanu Sekhar; Biswas, Chaitalee; Roy, Krishna (International Journal of Occupational Safety and Health, 2012)
Background: Work related musculoskeletal disorders are a common cause of pain in female workers in brick manufacturing industries involved in sorting and stacking process. Objective: This study aims to categorize the component of neuropathic and/or nociceptive pain with reference to chronic low back pain, its probable causes and its impact on functional variables like hand grip strength, number of man days lost etc. Methods: Female subjects [n=220] in the age range of 28-45 years from different brick fields of Hooghly and Birbhum district of West Bengal ,India with a work experience of more than 10 years participated in this study. Pain categorization was done by PAIN DETECT TOOL .Hand Grip dynamometry done to evaluate grip strength. NIOSH equation was used to standardize RWL. Results: It showed that pain/discomfort was mainly at the low back(90%),neck(72%) and wrist(62%).72% of workers had a pain of >20 in the pain scale of the pain detect tool & 80% of workers were not satisfied with treatments with analgesics/antipyretics which indicate the involvement of neuropathic component of pain in them. The impact of pain was revealed on functional and productivity endpoints like reduced grip strength which also lead to absenteeism, loss of average man days[4.5/month] , injuries[in 33% of workers] and monotony[85% workers] Conclusion: The probable cause of the chronic low back pain may be due to radiculopathy from repetitive lifting of bricks over and above the Recommended Weight Limit [Lifting Index 1.8]. DOI: http://dx.doi.org/10.3126/ijosh.v2i2.6597 International Journal of Occupational Safety and Health, Vol 2. No 2 (2012) 38-43